Self Regulated Learning dan Dukungan Sosial dengan Prokrastinasi Akademik pada Mahasiswa di Masa Pandemi - Suroso Suroso; Niken Titi Pratitis; Reni Oktaviana Cahyanti; Farra Lailatus Sa’idah Sa’idah (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2021)
Abstract— Student academic procastination is a tendency to procrastinate in completing assignments so that it results in not completing assignments and even hindering his studies in Higher Education One of the causes of internal factors is the lack of strategy and self-regulation or self-regulation, while external factors that are also predicted to cause procastination are social support. This quantitative study was aimed at examining the relationship between self-regulated learning and social support and academic procrastination during the pandemic. Research respondents were 266 students of all majors from various public and private universities whose data were obtained through the google form scale, which was distributed through social media applications. The data analysis technique used is the non-parametric Spearman Brown technique and the parametric Pearson correlation technique. The results of data analysis showed that there was a significant correlation between self-regulated learning and academic procastination (sig.0.029) but there was no significant correlation between social support and academic procastination (sig. 0.903). Keywords: self regulated learning, social support, academic procastination Abstrak— Prokastinasi akademik mahasiswa merupakan kecenderungan perilaku menunda-nunda menyelesaikan tugas hingga berakibat tidak terselesaikannya tugas bahkan terhambat studinya di Perguruan Tinggi. Salah satu faktor internal penyebabnya adalah kurangnya strategi dan pengaturan diri atau regulasi diri (self regulated) sementara faktor eksternal yang juga diprediksi dapat menyebabkan prokastinasi adalah, dukungan sosial. Penelitian kuatitatif iniditujukan untuk menguji hubungan antara self regulated learning dan dukungan sosial dengan prokrastinasi akademik dimasa pandemi. Responden penelitian adalah 266 orang mahasiswa semua jurusan dari berbagai universitas negeri maupun swasta yang datanya diperoleh melalui skala google form, yang disebarkan melalui aplikasi media sosial. Teknik analisis data yang digunakan yaitu teknik non parametric spearman brown dan teknik parametric pearson correlation. Hasil analisis data menunjukkan bahwa terdapat korelasi yang signifikan antara self regulated learning dengan prokastinasi akademik (p= 0,029) tetapi tidak ada korelasi yang signifikan antara dukungan sosial dengan prokastinasi akademik (p= 0,903). Kata kunci : self regulated learning, dukungan sosial, prokastinasi akademik